Analisis Faktor-faktor yang Memengaruhi Kecurangan (Fraud) pada Sektor Pemerintahan - Amanda Elsa Vionora Pitoyo; Dwi Suhartini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to examine and analyze the influence of compensation alignment, the effectiveness of internal control, organizational culture, and organizational commitment on fraud based on the perceptions of government employees in the City of Kediri. The research was conducted across all sub-districts in the City of Kediri, resulting in 138 respondents responsible for managing the financial reports of the sub-districts, consisting of the Head of the Sub-District, the Sub-District Secretary, and the Sub-District Treasurer, based on predetermined sample characteristics. This quantitative study employs Structural SEM-PLS analysis technique using SmartPLS 4.0 as the analytical tool. The study's findings indicate that fraud can be suppressed through compensation alignment and effective internal management countermeasures. However, organizational culture and commitment did not show a significant effect on suppressing fraud in the government sector. These findings are expected to serve as a consideration for the government of the City of Kediri to detect and implement early preventive measures to minimize fraud in the public sector.